The level of physical preparedness of students of higher educational institutions as a prerequisite of modular training - Volodymyr Faidevych (Kazimierz Wielki University, 2015)
Faidevych Volodymyr. The level of physical preparedness of students of higher educational institutions as a prerequisite of modular training. Journal of Education, Health and Sport. 2015;5(6):87-94. ISSN 2391-8306. DOI 10.5281/zenodo.18330 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A87-94 https://pbn.nauka.gov.pl/works/563528 http://dx.doi.org/10.5281/zenodo.18330 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 05.06.2015.   THE LEVEL OF PHYSICAL PREPAREDNESS OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS AS A PREREQUISITE OF MODULAR TRAINING   Volodymyr Faidevych   Lesya Ukrainka Eastern European National University, Lutsk, Ukraine   Summary A persistent deterioration in the health of the population and, in particular, students can be observed in recent times. Having entered into conflict with the real needs of renewal of society, the system of physical education of youth gave rise to the crisis. One of the key problems is changing of explanatory, illustrative and reproductive types of training in intensive technologies. On the basis of the analysis results established that the physical preparedness of students corresponds to the low level of development and is at a low and medium level. 42.9% of students have low level of physical preparedness, 36% of students physical preparedness is at a satisfactory level, and only 21.1% of students have a "high" level of physical preparedness. It means the need for modification of the system of methods, forms and means of teaching physical culture of students for improving the level of fitness. This situation leads to search for new, student-oriented teaching methods of physical training, in which students' interests would be taken into account. Modular training system occupies a central place among them. The methodology of modular training must be based on the following key provisions: individualization of means and methods of training, increasing volume and intensity of training lessons, accented development of motor skills and on the basis of their motor skills and interest in physical culture. The methodology eliminates the excessive detail, revealing the space for creativity of the teacher, increases the role of complex problem solving.   Key words: students, physical culture, modular training, physical preparedness.